Filosofskie motivy v istoričeskom romane Slovenii XX veka - Starikova, Nadežda Nikolaevna (Slavistična revija, 2006)
One of the most developed and quantitatively dominant genres in the twentieth-century Slovene literature is the historical novel, which is realized in various typological modifications. Philosophical issues are essential to its historical-philosophical variant. These motifs are most prominent in the novels Alamut (1938) by V. Bartol and Galjot (1978) by D. Jančar. The former combines features of intellecutal, philosophical, and psychological novels, the latter emphasizes the existence of the protagonist with respect to the particular historical period.
Keywords: Bartol, Vladimir; filozofija; historical novel; Jančar, Drago; philosophy; roman; Slovene literature; Slovene writers; slovenska književnost; slovenski pisatelji; zgodovinski roman